VapC6, a ribonucleolytic toxin regulates thermophilicity in the crenarchaeote Sulfolobus solfataricus - Maezato, Yukari (Cold Spring Harbor Laboratory Press, 2011)
The phylum Crenarchaeota includes hyperthermophilic micro-organisms subjected to dynamic thermal conditions. Previous transcriptomic studies of Sulfolobus solfataricus identified vapBC6 as a heat-shock (HS)-inducible member of the Vap toxin–antitoxin gene family. In this study, the inactivation of the vapBC6 operon by targeted gene disruption produced two recessive phenotypes related to fitness, HS sensitivity and a heat-dependent reduction in the rate of growth. In-frame vapBC6 deletion mutants were analyzed to examine the respective roles of each protein. Since vapB6 transcript abundance was elevated in the vapC6 deletion, the VapC6 toxin appears to regulate abundance of its cognate antitoxin. In contrast, vapC6 transcript abundance was reduced in the vapB6 deletion. A putative intergenic terminator may underlie these observations by coordinating vapBC6 expression. As predicted by structural modeling, recombinant VapC6 produced using chaperone cosynthesis exhibited heat-dependent ribonucleolytic activity toward S. solfataricus total RNA. This activity could be blocked by addition of preheated recombinant VapB6. In vivo transcript targets were identified by assessing the relative expression of genes that naturally respond to thermal stress in VapBC6-deficient cells. Preferential increases were observed for dppB-1 and tetR, and preferential decreases were observed for rpoD and eIF2 gamma. Specific VapC6 ribonucleolytic action could also be demonstrated in vitro toward RNAs whose expression increased in the VapBC6-deficient strain during heat shock. These findings provide a biochemical mechanism and identify cellular targets underlying VapBC6-mediated control over microbial growth and survival at temperature extremes.